"But Dr Google said…" – Training medical students how to communicate with E-patients. (2nd December 2019) - Herrmann-Werner, A.; Weber, H.; Loda, T.; Keifenheim, K. E.; Erschens, R.; Mölbert, S. C.; Nikendei, C.; Zipfel, S.; Masters, K.
Abstract: Purpose: Patients who have access to information online may feel empowered and also confront their physicians with more detailed questions. Medical students are not well-prepared for dealing with so-called "e-patients." We created a teaching module to deal with this, and evaluate its effectiveness. Method: Senior medical students had to manage encounters with standardized patients (SPE) in a cross-over design. They received blended-learning teaching on e-patients and a control intervention according to their randomization group (EI/LI = early/late intervention). Each SPE was rated by two blinded video raters, the SP and the student. Results: N = 46 students could be included. After the intervention, each group (EI, LI) significantly improved their competency in dealing with e-patients as judged by expert video raters (EI: M T0  = 9.75 (2.51) versus M T1  = 16.60 (2.80); LI: M T0  = 8.70 (2.14) versus M T2  = 15.20 (2.84); both p < 0.001) and SP (EI: M T0  = 24.13 (4.83) versus M T1  = 26.52 (3.06); LI: M T0  = 23.37 (3.10) versus M T2  = 27.47 (4.38); both p < 0.001). Students' rating showed a similar non-significant trend. Conclusions: Students, SP and expert video raters determined that blended-learning teaching can improve students' competencies when dealing with e-patients. Within the study period, this effect was lasting; however, further studies should look at long-term outcomes.